Kinerja Angkutan Umum di Kota Palu - M. Nurhidayat; Nini Apriani Rumata; Fathurrahman Burhanuddin; Didiet Haryadi Hakim; Soemitro Emin Praja (Universitas Muslim Indonesia, 2023)
Transportation has a very important role in supporting community activities. One mode of transportation that plays a very important role in supporting community activities is public transportation which functions to transport people from one place to another. In terms of public transport services, it often becomes a problem in the transportation system. Public transport in this case has a service role and function so that it is necessary to conduct a study to see the performance of public transport. In order to complete the analysis of the performance of public transport, a survey of load factor, headway, arrival frequency of public transport, travel time, and availability of public transport fleets is carried out. Analysis was carried out on several variables such as load factor, headway, frequency of public transport arrivals, travel time, and availability of public transport fleets based on applicable standards. This study aims to determine the performance of public transportation in the city of Palu on service to the community as transportation users.